Research Trends of Physics Identity Development in University: How About Indonesia? - Putri Dwi Sundari; Hidayati Hidayati (Jurnal Penelitian Pendidikan IPA, 2023)
The concept of physics identity plays an essential role for physics teacher professionalism. That is why physics identity development has become a trend of research in West country. Through this study, we aimed to analyze research related to physics identity development in various international journals. We reviewed 17 emphirical studies published in 2013-2023 in reputable journals in context of undergraduate physics. The findings of the study were discussed based on in what ways student’s physics identity development, and what factor that influences the development. We indentify gaps in the existing knowledge base, particularly in Indonesia context, and we purpose further study directions. This study provides an overview of how physics identity development in university and give information where is Indonesia position.